Clinical Integration of Next Generation Sequencing: A Policy Analysis. (2014) - Kaufman, David; Curnutte, Margaret; McGuire, Amy L.
Abstract : In 1996, President Clinton offered a promissory vision for human genetics when he said: "I think it won't be too many years before parents will be able to go home from the hospital with their newborn babies with a genetic map in their hands that will tell them, here's what your child's future will likely be like." The rapid evolution of genetic sequencing technologies has advanced that vision. In October 2006, the cost of sequencing an entire human genome was $10.4 million; by 2014 the cost had decreased a thousand fold. The term next generation sequencing (NGS) describes a variety of laboratory methods that allow efficient determination of the precise order of nucleotides in a DNA sequence. The papers in this issue of the Journal of Law, Medicine & Ethics focus on "clinical NGS, " which refers to rapid DNA sequencing using second-, third- and fourth-generation sequencing technologies to perform genome-wide sequencing of multiple genes or alleles for clinical prognostic, diagnostic, and therapeutic purposes.